2020
DOI: 10.35762/aer.2020.42.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton-Water Quality Relationship in Water Bodies in the Mekong Delta, Vietnam

Abstract: The study was conducted in March 2019 in three areas subject to impacts of agricultural production, residential areas and landfill in An Giang (Area 1), Kien Giang (Area 2) and Can Tho (Area 3), respectively, to assess relationship between water quality and diversity of phytoplankton. The results showed that water quality at 25 study sites is contaminated with organic matters, suspended solids and coliforms. The study found 422 species of phytoplankton belonging to five phyla of Bacillariophyta, Chlorophyta, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
4
17
0
Order By: Relevance
“…All pH values in locations from TT1 to HB2 in 2018 and 2019 in the canals in Ninh Kieu district, Can Tho city were within the allowable limit of column A (pH = 6-8.5) of QCVN 08-MT: 2015/BTNMT. Similar to the other studies, pH in the main rivers and tributaries of Hau River in 2016 fluctuated from 6.3-8.0 (Lien et al, 2016) and the water bodies in the Mekong delta from freshwater to saline water from 7.27-7.92 (Giao and Nhien, 2020;Giao, 2020). pH and temperature do not highly fluctuate in the water bodies in Ninh Kieu district since it is common condition in tropical region (Chounlamany et al, 2017).…”
Section: Nguyen Thanh Giaosupporting
confidence: 76%
See 1 more Smart Citation
“…All pH values in locations from TT1 to HB2 in 2018 and 2019 in the canals in Ninh Kieu district, Can Tho city were within the allowable limit of column A (pH = 6-8.5) of QCVN 08-MT: 2015/BTNMT. Similar to the other studies, pH in the main rivers and tributaries of Hau River in 2016 fluctuated from 6.3-8.0 (Lien et al, 2016) and the water bodies in the Mekong delta from freshwater to saline water from 7.27-7.92 (Giao and Nhien, 2020;Giao, 2020). pH and temperature do not highly fluctuate in the water bodies in Ninh Kieu district since it is common condition in tropical region (Chounlamany et al, 2017).…”
Section: Nguyen Thanh Giaosupporting
confidence: 76%
“…Population growth, production and services, agricultural activities are the major causes of surface water pollution. Former studies revealed that surface water quality in large and small rivers in the mekongd delta of Vietnam was seriously polluted (Lien et al, 2016;Ly and Giao, 2018;Tuan et al, 2019;Giao, 2020, Giao andNhien, 2020).…”
mentioning
confidence: 99%
“…In particular, the average TSS concentration in Hau River and in-field canals varied from 34.8±22.6 to 50.8±26.6 mg/L and 32.8±6.4 to 101.8±40.9 mg/L, respectively; this indicated that the water quality in Hau River was less polluted by TSS than those of the canals in Hau Giang Province. The high TSS concentration was due to rainwater runoff, erosion and the presence of phytoplankton in the environment (MONRE, 2012;Giao and Nhien, 2020). The concentration of TSS in Hau River in 2016 was higher than the current study (51.5±31.37 mg/L) (Lien et al, 2016); however, this concentration tended to be similar in 2018 (Giao, 2020).…”
Section: Surface Water Quality In Hau Giang Province In 2019mentioning
confidence: 66%
“…The DO value on the in-field canal in the current study was relatively large ranging from 3.2±0.1-5.2±0.8 mg/L and in Hau River ranged from 4.6±0.2-4.7±0.1 mg/L, the annual average was 4.0±0.3 mg/L, there may be negative effects on aquatic ecosystem life (Gebreyohannes et al, 2015). DO concentration in the canals had a tendency of being lower than in Hau River, because the concentration of DO depends on the air diffusion into the water, turbulence in rivers, the presence of biodegradable organic matters and the photosynthesis of phytoplankton (Giao and Nhien, 2020). DO concentration in Soc Trang Canals was 1.7 to 6.2 mg/L (Tuan et al, 2019); in the in-field canals of An Giang was in the range of 4.9-5.5 mg/L in the period from 2009-2016 (Ly and Giao, 2018).…”
Section: Surface Water Quality In Hau Giang Province In 2019mentioning
confidence: 99%
See 1 more Smart Citation